On the Lifeline Game of the Inertial Players with Integral and Geometric Constraints - Bahrom Samatov; Gafurjan Ibragimov; Bahodirjon Juraev; Massimiliano Ferrara (Mathematics, 2023)
In this paper, we consider a pursuit–evasion game of inertial players, where the pursuer’s control is subject to integral constraint and the evader’s control is subject to geometric constraint. In the pursuit problem, the main tool is the strategy of parallel pursuit. Sufficient conditions are obtained for the solvability of pursuit–evasion problems. Additionally, the main lemma describing the monotonicity of an attainability domain of the evader is proved, and an explicit analytical formula for this domain is given. One of the main results of the paper is the solution of the Isaacs lifeline game for a special case.